2020
DOI: 10.9734/ijpss/2020/v32i1230353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mono-Ammonium Phosphate and K-Humate Applications on Grain Yield and Phosphorus Uptake Efficiency of Bread Wheat Crop (Triticum aestivum L.)

Abstract: Study was aimed to determine the effect of mono-ammonium phosphate (MAP, NH4H2PO4) and K-Humate application on grain yield and grain phosphorus uptake efficiency which applied on Central Anatolian calcareous and basic reaction soil. The research was conducted at Bahri Dağdaş Agricultural Research Institute field in dry conditions during 2018 - 19 to determine the effect of phosphorus doses @ 0, 17.5 and 35.0 kg ha-1 and K-Humate @ 0 and 12 kg ha-1 on Bayraktar 2000 variety of bread wheat crop grain yield, agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Also, when the doses of ADP and DAP fertilizers increased, that means in popcorn at ADP and bread wheat at ADP, and the physiological efficiency of DAP phosphorus (PPUE) was decreased, and generally, ADP was better than DAP as well. Finally, phosphorus use efficiency decreased when increased phosphorus doses decreased, and ADP was generally better than DAP (Gezgin and Yossif, 2019; Yossif and Gezgin, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Also, when the doses of ADP and DAP fertilizers increased, that means in popcorn at ADP and bread wheat at ADP, and the physiological efficiency of DAP phosphorus (PPUE) was decreased, and generally, ADP was better than DAP as well. Finally, phosphorus use efficiency decreased when increased phosphorus doses decreased, and ADP was generally better than DAP (Gezgin and Yossif, 2019; Yossif and Gezgin, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…In the transition to organic agriculture, organomineral fertilizers have created an alternative in plant production. In the last decades, many studies have been reported that detect yield and quality increases in plant production in many countries in the transition to organomineral fertilizers (Namlı et al, 2019;Toprak, 2019;Mounirou et al, 2020;Yossif and Gezgin, 2020). Organomineral fertilizers are composed of both mineral fertilizers and organic fertilizers in certain proportions.…”
Section: Introductionmentioning
confidence: 99%
“…Organomineral fertilizers are composed of both mineral fertilizers and organic fertilizers in certain proportions. With the addition of organomineral fertilizers to the soil, both the mineral-rich chemical fertilizers easily supply the nutrients needed by the plant, while the organic matter in the organomineral fertilizer causes the rhizosphere to be improved and the nutrients offered by the chemical fertilizers to be benefited by the plant much more easily (Süzer and Çulhacı, 2017;Mounirou et al, 2020;Yossif and Gezgin, 2020). Phosphorus fertilizers, on the other hand, are plant nutrients that are highly related to the yield elements in the soil and ultimately to the plant's nutrition (Bai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the transition to organic agriculture, the use of organomineral fertilizers has created an alternative in plant production. In the last decades, many studies have been reported that detect yield and quality increases in plant production in many countries in the transition to organomineral fertilizers (Namlı et al, 2019;Toprak, 2019;Mounirou et al, 2020;Yossif and Gezgin, 2020). Organomineral fertilizers are composed of both mineral fertilizers and organic fertilizers in certain proportions.…”
Section: Introductionmentioning
confidence: 99%
“…Organomineral fertilizers are composed of both mineral fertilizers and organic fertilizers in certain proportions. With the addition of organomineral fertilizers to the soil, both the mineral-rich chemical fertilizers easily supply the nutrients needed by the plant, while the organic matter in the organomineral fertilizer causes the rhizosphere to be improved and the nutrients offered by the chemical fertilizers to be bene ted by the plant much more easily (Süzer and Çulhacı, 2017;Mounirou et al, 2020;Yossif and Gezgin, 2020).…”
Section: Introductionmentioning
confidence: 99%